A systematic review into patient reported outcomes following pancreaticoduodenectomy for malignancy. Issue 5 (May 2021) - Patel, Bhavik Y.; White, Laura; Gavriilidis, Paschalis; Satyadas, Thomas; Frampton, Adam E.; Pai, Madhava
Abstract: Background: Pancreaticoduodenectomy is associated with high rates of morbidity. This combined with the psychological burden of cancer, may impact on a patient's quality of life (QoL), which can be measured by using patient-reported outcomes (PRO). Objective: To perform a systematic review to evaluate the measurement of PRO after pancreaticoduodenectomy for cancer. Methods: 7 different databases were searched using 2 groups of search terms, one relating to pancreaticoduodenectomy, and one to PRO. Three authors screened the search results independently in a systematic manner based on predefined inclusion and exclusion criteria. Results: 27 studies, with 2173 eligible patients were included in the final analysis. Most of the included studies used validated instruments. The European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 questionnaire was most popular and used in 12 studies. The methodology of all included studies was also scrutinised. 12 studies were deemed to have high quality methodology according to pre-defined criteria. Conclusion: The instruments and methods used to measure PRO are variable. The quality of PRO within the available literature has improved over time, as has the number of studies measuring PRO. PRO should be measured with uniformity in future trials so that patients can be provided with more comprehensive information regarding post-operative recovery and QoL during the shared decision-making process preoperatively. Abstract : Pancreaticoduodenectomy is the operation used to resect cancers of the periampullary region, head of the pancreas and duodenum. This surgery can be associated with post-operative complications, which combined with the psychological burden of cancer, may impact on a patient's quality of life (QoL). Patient reported outcomes can be used to understand recovery from their perspective. The aim of this study is to evaluate the measurement of patient reported outcomes after pancreaticoduodenectomy within the available literature. Following a literature search of 7 databases 27 publications were included in the final review. In conclusion, there are different instruments available to measure patient reported outcomes. The quality of the included studies' methodology improved over time, as has the number of studies measuring patient reported outcomes. Future trials should aim to be more consistent so that data may be collated in the future to improve understanding of post-operative recovery and QoL.